La Ville/Paysage. Une nouvelle configuration pour les environnements de vie contemporaine - Giorgio Pizziolo; Rita Micarelli (VertigO)
The Contemporary environments, with their inhabitants, users and local governments, need new methodologies and procedures to cope with the difficulties of this transition period that concerns the relationships among the Ternary Systems - Individual/Social/Environmental- that are the basis of any urban-rural and territorial transformation. New participatory processes, procedures and ecological interactions can emerge from such Contemporary Ternary Systems and produce new configurations of the Life Environment, towards the Landscape/City.